2012
DOI: 10.1016/j.neuroimage.2012.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Causal Modelling of epileptic seizure propagation pathways: A combined EEG–fMRI study

Abstract: Simultaneous EEG–fMRI offers the possibility of non-invasively studying the spatiotemporal dynamics of epileptic activity propagation from the focus towards an extended brain network, through the identification of the haemodynamic correlates of ictal electrical discharges. In epilepsy associated with hypothalamic hamartomas (HH), seizures are known to originate in the HH but different propagation pathways have been proposed. Here, Dynamic Causal Modelling (DCM) was employed to estimate the seizure propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…While our patient stated that he neither especially liked nor disliked rap music, he indicated that the auras were accompanied by a rather unpleasant feeling, which might find its correlate in the activation of the right mesial temporal lobe during the seizure. DCM for fMRI has already been successfully used to investigate effective connectivity in epileptic networks identified with EEG-fMRI on a single-subject patient-specific level (Murta et al, 2012;Vaudano et al, 2012Vaudano et al, , 2013 as well as in a small group of patients with idiopathic generalized epilepsy (Vaudano et al, 2009). In these cases, the primary source and propagation pathway of epileptic discharges from fMRI data were determined by testing a set of clinically plausible network connectivity models.…”
Section: Dynamic Causal Modelingmentioning
confidence: 99%
“…While our patient stated that he neither especially liked nor disliked rap music, he indicated that the auras were accompanied by a rather unpleasant feeling, which might find its correlate in the activation of the right mesial temporal lobe during the seizure. DCM for fMRI has already been successfully used to investigate effective connectivity in epileptic networks identified with EEG-fMRI on a single-subject patient-specific level (Murta et al, 2012;Vaudano et al, 2012Vaudano et al, , 2013 as well as in a small group of patients with idiopathic generalized epilepsy (Vaudano et al, 2009). In these cases, the primary source and propagation pathway of epileptic discharges from fMRI data were determined by testing a set of clinically plausible network connectivity models.…”
Section: Dynamic Causal Modelingmentioning
confidence: 99%
“…Prior work has also employed DCM analysis to examine hypothalamic efferents and epileptogenic signal propagation in hamartoma-related seizure (Murta et al, 2012). There, directionality was resolved by measuring ascending and descending pathways, with concurrent consideration of corticocortical connections.…”
Section: Box 2 Ongoing and Completed Trials For The Development Of Dbmentioning
confidence: 99%
“…This recent DCM analysis of seizure progression offers a nice analogy to the questions one could pose regarding abnormal AD pathways that link cortical and/or subcortical regions. Murta et al (2012) tested long-standing and competing hypotheses regarding the pathways and epileptic signal propagation from hypothalamic regions to frontal regions in a single patient with hypothalamic hamartoma-induced seizures. Using DCM for fMRI, they found that the probable connectivity architecture involved a pathway from the hypothalamus to frontal cortex via a cingulate region, rather than a direct projection from hypothalamus to frontal cortex.…”
Section: Box 2 Ongoing and Completed Trials For The Development Of Dbmentioning
confidence: 99%
“…Over the past two decades, the simultaneous acquisition of the electroencephalogram (EEG) with functional magnetic resonance imaging (fMRI) has had an important role in the investigation of human brain function, particularly in the clinical context of epilepsy (Ritter and Villringer 2006;Laufs 2008;Vulliemoz et al 2010;Gotman and Pittau 2011;Murta et al 2012;Chaudhary et al 2013). This noninvasive multimodal imaging technique has been particularly useful for the mapping of haemodynamic changes over the whole brain associated with spontaneous activity (including inter-trial variability) observed on EEG, taking advantage of the complementary nature and spatiotemporal properties of the EEG and fMRI signals (Rosa et al 2010a;Jorge et al 2013).…”
Section: Introductionmentioning
confidence: 99%